Qualitative analysis on the barriers of industrialised building system (IBS) uptake in Malaysian construction projects - Nawi, M.N.M; Shaharanee, I.N.M; Hashim, K.F.; Azman, M.N.A.; Ibrahim, S.H. (American Scientific Publishers, 2015)
Even though the construction industry is very competitive, it is currently very labor intensive. As such the Malaysian Government has been continuously encouraging the industry to use the Industrialised Building System (IBS), which is considered to be an important part of modern method construction approach. However, the system has so far failed to gather momentum especially among the private construction projects. Accordingly, many studies have been conducted for identifying the factors that contributed to this problem. However, the previous studies mostly focused on the qualitative data whereas the finding has limited discuss on ‘how’ and ‘why’ of the problem happened. Based on the findings from the industry workshop, this paper discusses the identified barriers with the aim of examining how far these barriers may well affect the process of IBS implementation in the Malaysian construction industry.